Analyzing and Aggregating Visitor Tracks in a Protected Area (Quality Aspects in Spatial Data Mining, 2009)
In recent decades, recreational use of natural areas has grown rapidly from lowintensity and relatively passive use to a situation where tourism is the dominant force driving change in many rural areas and their associated communities (Butler et al., 1998). However, excessive use of natural areas can have significant direct and indirect negative impacts. These include both environmental degradation (Farrell and Marion, 2001) and diminishing quality of the visitors’ recreational experience (Lynn20.1 Introduction ...265 20.1.1 Motivation and Context ...265